LATE BLIGHT DISEASE OF POTATO AND ITS MANAGEMENT - Arora, RK; Sharma, Sanjeev; Singh, BP (Potato Journal, 2014)
Late blight caused by Phytophthora infestans is one of the most dreaded diseases of potato worldwide and cause significant loss in production. The pathogen is highly variable and adapt to the newly bred varieties and fungicides. Population of P. infestans in most of the countries has changed dramatically and original A1 has almost been displaced by more virulent A2 strain. In India, A2 mating type was recorded in 1990s and now it has displaced the A1 in temperate highlands while in sub-tropical plains still A1 is dominating. Virulence to all major resistance genes has been recorded and in India the racial complexity has reached to its zenith resulting in breakdown of many disease resistant varieties. Indiscriminate use of metalaxyl based fungicides has led to the development of metalaxyl resistance world over including India, which has necessitated the use of additional systemic molecules for the management of this disease. The population of P. infestans characterized using molecular markers has led to better understanding of pathogen at molecular level. Mitochondrial DNA haplotyping of P. infestans has revealed that mt Ia is displacing the other haplotypes globally at a faster rate including India. Relationship between P. infestans and the weather is well understood and has been utilized for developing disease forecasting models and decision support systems across the globe including India. An increasing severity of late blight in many potato growing areas, a shift in pathogen population toward increased specific virulence and an increasing tolerance to the most effective late blight specific fungicides suggests a need to develop an appropriate disease management strategy based on information technology.